Macrozoobenthos and environmental changing in the Venice Lagoon (Italy) - Cacciatore, Federica; Cornello, Michele; Bernarello, Valentina; Oselladore, Federica; Novello, Marta; Girolimetto, Alessandra; Zorzi, Massimo; Bon, Daniele; Strazzabosco, Fabio; Bonometto, Andrea; Boscolo Brusà, Rossella (Frontiers in Marine Science, 2025)
Macrozoobenthos are invertebrates playing a fundamental role in the ecosystem processes of several environments, such as lagoons. They contribute to nutrient cycles, metabolization of pollutants, sediment oxygenation, as well as filtering phytoplankton, and are a food source for other organisms at higher level of the food web. The distribution of macrozoobenthos depends on both abiotic and biotic factors, such as salinity, depth, hydrodynamics, sediment size and composition, as well as inter- and intraspecific competition and predation. Macrozoobenthos communities are commonly used as bioindicators to assess the quality of coastal and transitional marine ecosystems. In fact, they represent one of the biological quality elements for evaluating the ecological quality status of transitional and coastal waters under the Water Framework Directive. The aim of this study is to investigate changes in the macrozoobenthos community and their relationship with environmental parameters in the Venice Lagoon, one of the largest and most important transitional water bodies in the Mediterranean Sea. To this end, ecological indices were applied to 268 samples and 252 taxa, collected from 2011 to 2022, with macrozoobenthos sampled once every three years during the spring-summer period. Trends in environmental conditions of the water coloumn (sampled seasonally each year) and sediments (sampled concurrently with macrozoobenthos) were also analyzed, highlighting a significant increase/decrease in some parameters, which were then related to dissimilarities in macrozoobenthos abundances. The results show that the macrozoobenthos community in the Venice lagoon has changed over time, with evidence of biodiversity loss and differences between polyhaline and euhaline areas, and between different hydrodynamic zones. The changes in macrozoobenthos are also significantly related to environmental parameters such as salinity, temperature, nutrients, organic carbon, silicate, and grain size.